2016
DOI: 10.3847/0004-637x/829/1/10
|View full text |Cite
|
Sign up to set email alerts
|

A Polytropic Model for Space and Laboratory Plasmas Described by Bi-Maxwellian Electron Distributions

Abstract: Non-local electron energy probability functions (EEPFs) are shown to have an important effect on the thermodynamic behavior of plasmas in the context of solar wind and laboratory plasmas. A conservation relation is held for electron enthalpy and plasma potential during the electron transport. For an adiabatic system governed by non-local electron dynamics, the correlation between electron temperature and density can be approximated by a polytropic relation, with different indexes demonstrated using three cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Little and Choueiri [33] suggested the possibility of performance improvements, arguing that the particle motion does not correspond to adiabatic cooling, but rather isothermal behavior reflected in the excessively small Nusselt number in which electron heat conduction along the magnetic field overwhelms convection, which was originally derived by Litvinov [35]. On the contrary, Zhang et al [34,36] concluded that the nozzle device with electric double layer is already in adiabatic expansion, which ensures no heat transfer into the system, and non-local electron kinetics very far from a local thermodynamic equilibrium for a nearly collisionless plasma is responsible for the low γ e value. Recently, there has been an attempt to investigate the relationship between the thermodynamic change of the electrons, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Little and Choueiri [33] suggested the possibility of performance improvements, arguing that the particle motion does not correspond to adiabatic cooling, but rather isothermal behavior reflected in the excessively small Nusselt number in which electron heat conduction along the magnetic field overwhelms convection, which was originally derived by Litvinov [35]. On the contrary, Zhang et al [34,36] concluded that the nozzle device with electric double layer is already in adiabatic expansion, which ensures no heat transfer into the system, and non-local electron kinetics very far from a local thermodynamic equilibrium for a nearly collisionless plasma is responsible for the low γ e value. Recently, there has been an attempt to investigate the relationship between the thermodynamic change of the electrons, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it expands isothermally, implying that heating of the plasma occurs as it propagates through interplanetary space [4][5][6]. Many laboratory experiments under adiabatic conditions [7][8][9] have also shown a nearly isothermal expansion with γ ∼ 1.0 − 1.2 in magnetic nozzles, and the relation with astrophysical plasmas has been discussed [10]. However, in these expanding adiabatic systems, it appears that electric fields may have a significant nonlocal effect on the dynamics of the electrons; many of them are trapped in the system by the ambipolar and wall sheath electric fields, allowing an isothermal equilibrium to be established after sufficient time has elapsed, while some of the electrons having the energy overcoming the potential drop can escape from the system.…”
mentioning
confidence: 99%
“…Finally, the thermal speed was set to increase with the plasma density according to the adiabatic relationship (i.e., v th ∝ n 1/3 ), which is widely used to describe space plasmas within the heliosphere (e.g., Parker 1961;Zhang et al 2016). We then constructed the VDFs in the Cartesian instrument frame with resolution ∆u x ×∆u y ×∆u z = 500 × 500 × 500 km 3 s −3 and analyzed them as explained in Sections 3.4 and 3.5 to derive the electron bulk parameters.…”
Section: Model Resultsmentioning
confidence: 99%